Psilocybin-Assisted Compassion Focused Therapy for Depression - Pots, Wendy; Chakhssi, Farid (Frontiers in Psychology, 2022)
Psilocybin-assisted psychotherapy, i.e. psilocybin treatment with psychological support, has demonstrated the efficacy of psilocybin to reduce depressive symptoms. However, in clinical trials, the structure of psilocybin-assisted psychotherapy is primarily based on preparation, navigation (support during dosing sessions), and integration. For the psychotherapeutic guidance, the application of this structure is favored over the usage of theoretical models. The applied psychotherapeutic models may be of critical importance if the effects are augmented due to the psychologically insightful experiences during the navigation and integration sessions. One of the important next steps is to provide therapists with guidance on how to provide psilocybin-assisted psychotherapy. We present an integrated protocol for psilocybin-assisted psychotherapy for depression based on the theoretical model and psychotherapeutic framework of Compassion Focused Therapy (CFT). We hypothesize that CFT can provide the theoretical model and compassion practices that will reinforce the experiences during the navigation and follow-up therapy sessions. In this paper, we describe the rationale for selecting CFT, the compatibility of CFT and psilocybin-therapy, an overview of the psilocybin-assisted CFT protocol, the study protocol, and limitations to this approach.